Risk Factors and Outcomes of Klebsiella pneumoniae Infection Before and After Allogeneic Hematopoietic Cell Transplantation - Gavriilaki, Eleni; Sakellari, Ioanna; Chatzikonstantinou, Thomas; Mallouri, Despina; Batsis, Ioannis; Katsifa, Eleni; Papadimitriou, Stergios; Panteliadou, Alkistis; Baldoumi, Eirini; Demosthenous, Christos; Bousiou, Zoi; Constantinou, Varnavas; et al. (Frontiers in Medicine, 2021)
Objectives: Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae (KPC-Kp) emerge as a major healthcare concern worldwide. Despite the significance of infections before and after allogeneic hematopoietic cell transplantation (alloHCT), the burden of KP infections has not been extensively evaluated. Methods: We studied the incidence, risk factors, and outcomes of consecutive alloHCT recipients with Kp isolates before and after alloHCT. Results: Among 424 patients undergone alloHCT in 2008-2018, we studied two groups: those with Kp isolates before (Group 1, 52 patients) and those with Kp isolates after alloHCT (Group 2, 66 patients). Pre-transplant infections were associated with post-transplant infections (p=0.010), despite secondary prophylaxis. KPC-Kp was isolated in 29% of Group 1, and 80% of Group 2. Both groups were characterized by a significant burden of moderate-severe acute graft-versus-host-disease/GVHD (cumulative incidence/CI of 44.5% and 61.9% respectively) and severe chronic (CI of 56.7% and 61.9%). Kp infections and GVHD were independent predictive factors of treatment-related mortality (TRM) in both groups. Conclusions: Our study highlights the significant impact of Kp infections on TRM, with GVHD consisting an important underlying factor. Since prophylactic measures did not improve rates of post-transplant infections, innovative interventions need to be further investigated to address this major healthcare concern.